Revisión Bibliográfica Sobre el Tratamiento Sistémico y Cognitivo Conductual Del Trastorno Límite de Personalidad (2016)
This research aims to conduct a literature review on the cognitive behavioral and systemic treatment of borderline personality disorder. Considering that the therapy recognized by the APA in the year 2001 for the treatment of this disorder is the therapy for Dialectical Behavior, belonging to the theoretical perspective Cognitive Behavioral. And which according to Rodríguez Moya & Peláez (2013), through the study of Masterson and Rinsley, it was suggested that the family could be involved in the development and maintenance of the disorder, so that in order to correct it, the family should be corrected.